Open Innovation as a Competitive Advantage, Process of Implementation - Čermáková Ivana; Činčalová Simona (International Business Information Management Association-IBIMA, 2016)
Nowadays, innovation is a very hot topic. The authors choose a part of it – open innovation, which is a trending theme in innovation management. Open innovation is the new imperative for creating and profiting from technology. The paper aims to define the basic concepts relating to innovation (how to make an innovation culture) and open innovation and to make a model of process how to take a change. Every innovation is a process of change and our model will be modified to open innovation.
Otevřená inovace jako konkurenční výhoda, proces její implementace
Keywords: innovation; open innovation; process of change; inovace; otevřená inovace; proces změny